PENGUASAAN BAHASA INGGRIS MAHASISWA BARU UNY TAHUN AKADEMIK 2005/2006 – 2009/2010 PADA KRITERIA TOEFL-LIKE - Sugeng, Bambang (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2012)
Four research questions are proposed related to (1) students’ English proficiencylevels at the university and faculty levels, (2) their English proficiency levels in each study program, (3) their proficiency in Listening, Structure, and Reading, and (4) possible activities as follows-ups of the TOEFL-Like tests. Using the survey research design, the study involved 24,909 YSU new students of the academic years 2005–2009. Data were analyzed quantitatively using the mean, standard deviation, frequency, and percentages. The results are as follows. First, on the university level, students attain a mean score of 367 (intermediate) with a standard deviation of 50.65 (high homogeneity). On the faculty level,they attain a mean score of 378.81 (FMIPA), 372.83 (FISE), 367.18 (FT), 363.83 (FBS), 363.77 (FIP), and 356.44 (FIK). Second, highest scores are achieved by four study programs (400 or higher), the second by 13 study programs (375 – 399), the third by 45 study programs (350 – 374), and the lowest scores by eight study programs (349 or lower). Third, the score attainment is 35.5% (Reading), 31.25% (Structure), and 27.2% (Listening). Fourth, possible follow-up activities are elevation of students’ TOEFL scores, course placements, improvement of MKU English, planning and implementation of international programs, and graduation requirement for S-1.